2007
DOI: 10.1002/ab.20198
|View full text |Cite
|
Sign up to set email alerts
|

The importance of narcissism in predicting proactive and reactive aggression in moderately to highly aggressive children

Abstract: The present study examined the importance of psychopathy-linked narcissism in predicting proactive and reactive aggression and conduct problems in a group of 160 moderately to highly aggressive children (mean age of 10 years, 9 months). Children's self-report of self-esteem and parent and teacher report of dimensions of psychopathy [narcissism, callous-unemotional (CU) traits, and impulsivity], proactive and reactive aggression, and conduct problems were collected. Composites of parent and teacher ratings of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
147
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(168 citation statements)
references
References 53 publications
17
147
1
2
Order By: Relevance
“…In addition, they showed that narcissism positively predicted conduct problems, after controlling for CU traits. In a second study using 160 at-risk youth (mean age 10 years, 9 months), narcissism was found to uniquely and positively predict proactive and reactive aggression, and conduct problems, after controlling for CU traits, and impulsivity (Barry, Thompson et al, 2007). In a third study utilizing a sample of at-risk 16 to 18 year olds, Barry, Grafeman and colleagues (2007), found narcissism to positively predict delinquency, overt aggression and relational aggression.…”
Section: Narcissismmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, they showed that narcissism positively predicted conduct problems, after controlling for CU traits. In a second study using 160 at-risk youth (mean age 10 years, 9 months), narcissism was found to uniquely and positively predict proactive and reactive aggression, and conduct problems, after controlling for CU traits, and impulsivity (Barry, Thompson et al, 2007). In a third study utilizing a sample of at-risk 16 to 18 year olds, Barry, Grafeman and colleagues (2007), found narcissism to positively predict delinquency, overt aggression and relational aggression.…”
Section: Narcissismmentioning
confidence: 99%
“…This combination of narcissistic traits with emotional and behavioral dysregulation may make youth especially unstable and volatile, committing acts of aggressive behavior as a result of intense anger and poor impulse control due to perceived slights to their self-image. This type of retaliatory aggressive behavior, also known as reactive aggression, has been previously associated with youth high in narcissistic traits (Barry, Thompson et al, 2007).…”
Section: Narcissistic Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, because individuals can often present with psychopathic traits before reaching the age of 18 years [13] there has been increasing numbers of studies conducted over the past decade using the term psychopathic traits [11,14]. This research shows that psychopathic traits in adolescent offenders are associated with more severe and persistent forms of antisocial behavior [15,16], greater versatility in offending, and higher rates of violent crimes [17] than in other offenders.…”
mentioning
confidence: 92%